Understanding cancer fatalism in communication: causes, effects, and interventions - Chen, Minyi (Nanyang Technological University, 2025)
Cancer is a leading cause of death worldwide, with a significant portion attributed to modifiable risk factors like unhealthy lifestyles. However, cancer prevention efforts often face challenges due to low compliance rates. A critical barrier to effective cancer prevention is cancer fatalism—the belief that a cancer diagnosis is predetermined and beyond individual control. This pessimistic outlook diminishes engagement in preventive behaviors. This thesis investigates cancer fatalism from a health communication perspective, examining its causes, effects, and potential interventions. The research aims to synthesize existing evidence, apply communication models to understand the emergence and consequences of cancer fatalism, explore the impact of exposure to conflicting cancer information, and develop effective strategies to combat cancer fatalism. Chapter One identifies gaps in the existing research on cancer fatalism, outlines the objectives of this thesis, and describes how subsequent chapters aim to bridge these gaps. Chapter Two presents Study 1, a meta-analysis synthesizing empirical results from 100 studies on the associations between cancer fatalism and four categories of communicative and behavioral correlates: media exposure, cancer beliefs, cancer prevention and detection engagement, and cancer information management. The findings reveal that specific media exposure is associated with higher cancer fatalism. Additionally, cancer fatalism is associated with lower engagement in preventive behaviors, highlighting its role as a psychological barrier to effective cancer prevention. Chapter Three presents Study 2, which employs a three-wave panel survey with a nationally representative sample of 1,118 Singaporean adults. Consulting the Extended Parallel Processing Model (EPPM), this study examines the associations between exposure to conflicting cancer information and cancer fatalism, cancer beliefs, and preventive behaviors. The results indicate that exposure to conflicting cancer information is associated with lower perceived efficacy, which, in turn, is associated with higher cancer fatalism and lower engagement in preventive behaviors. This chapter highlights the adverse effects of conflicting information environments on public health and emphasizes the need for targeted health campaign efforts to overcome them. Chapter Four details Study 3, which applies inoculation theory to address the issues identified in Study 2. This two-phase experiment involved 572 participants randomly assigned to read either a narrative inoculation message, a non-narrative inoculation message, or a control message. Participants’ ability to resist conflicting cancer information and cancer fatalism was assessed both immediately and after a two-week period. The findings confirm that inoculation messages, which provide preemptive counterarguments against conflicting information, effectively reduce cancer fatalism, enhance perceived efficacy in cancer prevention, and promote preventive behaviors. This study extends inoculation theory to address cultural beliefs and demonstrates its potential to mitigate the negative impact of conflicting health information. Collectively, these studies contribute to a comprehensive understanding of cancer fatalism within the context of health communication. They provide empirical evidence regarding the associations between conflicting information and health beliefs and behaviors, offering theoretical advancements that integrate media effects with cultural and psychological dimensions. The thesis also explores the potential of inoculation strategies to counteract negative media effects, suggesting practical applications for health campaigns aimed at promoting resilience against fatalistic beliefs. The theoretical and practical implications of the thesis are discussed in Chapter Five.